Meningkatkan Efisiensi Sistem Peradilan Dalam Menanggulangi Kejahatan Melalui Pembaharuan Hukum Acara Pidana - Erni Tyas Aryani (CV. Lenggogeni Data Publishing, 2024)
Criminal law reform is an important effort to increase the effectiveness of the justice system in dealing with crime. In this context, this literature study discusses several key aspects related to criminal law reform. First, this research will discuss the need for criminal law reform as a response to social, economic and cultural changes that influence crime rates. Second, this research will review various approaches that can be taken in criminal law reform, such as changes in sentencing arrangements, reform of judicial procedures, and increasing justice system resources. Third, this study will highlight the important role of the keywords